2019
DOI: 10.1007/s10339-019-00927-w
|View full text |Cite
|
Sign up to set email alerts
|

Now you see me, now you don’t: detecting sexual objectification through a change blindness paradigm

Abstract: The goal of this work is to provide evidence for the cognitive objectification of sexualized targets via a change blindness paradigm. Since sexual objectification involves a fragmented perception of the target in which individuating features (i.e., the face) have less information potential than sexualized features (i.e., body parts), we hypothesized that changes in faces of sexualized targets would be detected with less accuracy than changes in faces of nonsexualized targets. Conversely, we expected that chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Research using an eye tracker, a device that allows one to measure the location and the duration of people’s gaze when they view pictures, found that people looked at bodies of sexualized targets for more time and at their faces for less time (Cogoni, Carnaghi, Mitrovic, et al, 2018; Nummenmaa, Hietanen, Santtila, & Hyönä, 2012). Another study found that as a result of such preferential looking, people were less likely to notice perceptual changes targeting faces than perceptual changes targeting parts of sexualized bodies (Andrighetto et al, 2019). It is also worth noting that research uncovered that priming low social power, reducing the visibility of sexual parts, and providing information about targets’ personality can successfully counteract the cognitive objectification of sexualized bodies (Bernard et al, 2015; Civile & Obhi, 2016).…”
Section: Sexualization Affects the Way People See Othersmentioning
confidence: 99%
“…Research using an eye tracker, a device that allows one to measure the location and the duration of people’s gaze when they view pictures, found that people looked at bodies of sexualized targets for more time and at their faces for less time (Cogoni, Carnaghi, Mitrovic, et al, 2018; Nummenmaa, Hietanen, Santtila, & Hyönä, 2012). Another study found that as a result of such preferential looking, people were less likely to notice perceptual changes targeting faces than perceptual changes targeting parts of sexualized bodies (Andrighetto et al, 2019). It is also worth noting that research uncovered that priming low social power, reducing the visibility of sexual parts, and providing information about targets’ personality can successfully counteract the cognitive objectification of sexualized bodies (Bernard et al, 2015; Civile & Obhi, 2016).…”
Section: Sexualization Affects the Way People See Othersmentioning
confidence: 99%
“…This result was the first one to demonstrate how a sexualized woman is elaborated more analytically dividing her body in separate body parts as if she was an object. Perceiving objectified women as object-like rather than as a full human being has been linked to a shift in focus from the face to the female body, a process that was recently confirmed by Andrighetto et al (2019). These researchers implemented the change blindness paradigm showing how changes in the bodies of sexualized targets were more easily detected than changes in the bodies of non-sexualized targets, a difference that did not occur when the changes needed to be detected in the faces of these targets.…”
Section: Sexual Objectificationmentioning
confidence: 94%
“…Facial expressions represent a meeting point between affective and social dynamics, they have been employed as stimuli in numerous and connected research fields dealing with cognitive, social, and emotional processes, as well as emotional disorders and psychopathology. Interestingly, these same scientific fields have been studied within the realm of sexual objectification, that is, cognitive objectification (Andrighetto et al, 2019;Bernard et al, 2018;Vaes et al, 2019), the socialization and competition between women (Vaillancourt & Sharma, 2011), emotional mechanisms (e.g., empathy, Cogoni et al, 2018) and the negative psychological consequences of self-objectification related to emotional disorders and psychopathology (e.g., depression, social anxiety, eating disorders, Jones & Griffiths, 2015;Fredrickson et al, 1998). Taken together, it is evident how sexual objectification is a widespread phenomenon that can be linked to many other research areas: from its clinical ramifications, its links with mind and face perception studies, the analysis of its underlying cognitive mechanisms, to the area of emotion perception and recognition.…”
Section: Emotion Recognitionmentioning
confidence: 99%
“…Sexual objectification-the reduction of a person's value to their body or sexual body parts (Bartky, 1990)-affects perceptions, cognitions, and attitudes toward the objectified targets (e.g., Ruzzante et al, 2022) and causes numerous negative consequences for the victims (e.g., Roberts et al, 2017). Indeed, objectified targets, mostly women, are denied morality, mind, warmth, and competence (e.g., Heflick & Goldenberg, 2009;Loughnan et al, 2010), and they are elaborated similarly to real objects (Vaes et al, 2019), even at a cognitive level (see Bernard et al, 2020 for a recent review; see also Andrighetto et al, 2019). Thus, when sexual objectification occurs, targets are dehumanized and perceived as not (or less) worthy of moral treatment.…”
Section: Abstract Dating Violence Perceptions Of Domestic Violence Pr...mentioning
confidence: 99%